유아기 자녀를 둔 어머니들의 부모교육 내용에 대한 요구 - 이원영(Won Young Rhee); 배소연(So Youn Bae) (Korean Journal of child studies, 2000)
The purpose of this study was to identify needs of mothers in order to lay a foundation for improving the content of parent education in early childhood educational institutions. The mothers of 164 kindergarten children in Pusan participated in this study by a questionnaire developed by the researchers. Conclusions were that the felt needs of mothers identified in this study should be included in parent education programs along with knowledge, skills and attitudes selected by professionals. Selection of content should be based on the fact that most mothers have similar concerns and interest in raising their children, regardless of background. However, mother's educational level needs to be considered. Further study needs to be done on educational methods, and tentative models of parent education need to be designed in order to activate effective parent education.